Change Management in TVET Colleges Lessons Learnt from the Field of Practice - Kraak, André; Paterson, Andrew; Bok, Kedibone (African Minds, 2016)
The Technical and Vocational Education and Training (TVET) college environment is marked by increasingly stark juxtapositions between what needs to be achieved in the post-school education sector and the increasing difficulty of current conditions. The 'triple challenge' of poverty, inequality and unemployment weighs heavily on the social, political and economic fabric of the country and expectations are high that the TVET colleges can make a pivotal contribution to counter these challenges. Despite laudable increases in TVET enrolment, the education system needs to work harder to accommodate the weight of demand for post school further education and training (FET) band qualifications from young people not in education, employment or training. At the same time, it is vital to secure adequate quality in TVET programmes which depend so much on the competence and commitment of college lecturers.